Note-Taking: The Gender Difference on Students’ Perception - Muhimatul Murtafi'ah; Muflihah Muflihah; Evynurul Laily Zen (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Most of previous studies conducted on the implementation of note-taking strategy, finding its effect and the students’ preferent on the note-taking strategies. However, this study investigates whether there is any difference in the students’ perception on note-taking based on the gender differences. This study was conducted on the sixth semester of university students who had experienced implementing note-taking during the learning process by collecting the students’ perception on note-taking by using questionnaire and semi-structured interview as the data collection techniques. As this study investigated the comparison of both male and female students’ perception, the researchers used the quantitative research design. The result of this study indicates the opposite of most the previous studies have found. This result is not in line with the previous studies which discussed more below. Both male and female have a positive respond to the effectiveness of note-taking